Histopathology of Incontinence-Associated Skin Lesions: Inner Tissue Damage Due to Invasion of Proteolytic Enzymes and Bacteria in Macerated Rat Skin - Mugita, Yuko (PLoS One, 2015)
A common complication in patients with incontinence is perineal skin lesions, which are recognized as a form of dermatitis. In these patients, perineal skin is exposed to digestive enzymes and intestinal bacterial flora, as well as excessive water. The relative contributions of digestive enzymes and intestinal bacterial flora to skin lesion formation have not been fully shown. This study was conducted to reveal the process of histopathological changes caused by proteases and bacterial inoculation in skin maceration. For skin maceration, agarose gel containing proteases was applied to the dorsal skin of male Sprague-Dawley rats for 4 h, followed by Pseudomonas aeruginosa inoculation for 30 min. Macroscopic changes, histological changes, bacterial distribution, inflammatory response, and keratinocyte proliferation and differentiation were examined. Proteases induced digestion in the prickle cell layer of the epidermis, and slight bleeding in the papillary dermis and around hair follicles in the macerated skin without macroscopic evidence of erosion. Bacterial inoculation of the skin macerated by proteolytic solution resulted in the formation of bacteria-rich clusters comprising numerous microorganisms and inflammatory cells within the papillary dermis, with remarkable tissue damage around the clusters. Tissue damage expanded by day 2. On day 3, the proliferative keratinocyte layer was elongated from the bulge region of the hair follicles. Application of proteases and P. aeruginosa induced skin lesion formation internally without macroscopic erosion of the overhydrated area, suggesting that the histopathology might be different from regular dermatitis. The healing process of this lesion is similar to transepidermal elimination.